2008
DOI: 10.1186/1471-2458-8-381
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vaccination coverage in rural Nigeria

Abstract: Background: Childhood immunization is a cost effective public health strategy. Expanded Programme on Immunisation (EPI) services have been provided in a rural Nigerian community (Sabongidda-Ora, Edo State) at no cost to the community since 1998 through a privately financed vaccination project (private public partnership). The objective of this survey was to assess vaccination coverage and its determinants in this rural community in Nigeria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
187
6
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(259 citation statements)
references
References 13 publications
52
187
6
8
Order By: Relevance
“…Many studies have shown that maternal education or literacy is positively associated with the vaccination status of the children (1,6,8,9,13,25). In addition, some studies showed that the mother's knowledge of specific immunizations was associated with full vaccination (3,5,17). However, in Mali, Koumaré et al reported no difference associated with parental knowledge about EPI diseases and full vaccination (3).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that maternal education or literacy is positively associated with the vaccination status of the children (1,6,8,9,13,25). In addition, some studies showed that the mother's knowledge of specific immunizations was associated with full vaccination (3,5,17). However, in Mali, Koumaré et al reported no difference associated with parental knowledge about EPI diseases and full vaccination (3).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…They are considered one of the most important achievements in public health and one of the most cost-effective preventive services for children (1)(2)(3)(4)(5)(6)(7). The major contributor to this success is the Expanded Programme on Immunization (EPI) of the World Health Organization (WHO), United Nations Children's Fund (UNICEF) and Global Alliance Vaccine Initiative (GAVI) (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odusanya O O et al have reported that if parents could maintain a vaccination card, the child is more likely to get fully vaccinated. 6 In this study, though vaccine card was maintained by all of them (100%), some (14%) missed out one or more doses which could be due to other reasons mentioned earlier.…”
mentioning
confidence: 99%
“…knowledge has a great impact on the children's immunization rate and maintaining up-to-date immunization status (23,24).…”
Section: Discussion:-mentioning
confidence: 99%